Achieving high performance anticorrosive coating via in situ polymerization of polyurethane and poly(propylene oxide) grafted graphene oxide composites. (November 2020) - Xue, Dan; Meng, Qing Bo; Lu, Ying Xi; Liang, Lin; Wei, Yu Han; Liu, Xian Bin
Graphical abstract: Highlights: GO nanosheets are used to directly initiate ring-opening polymerization of propylene oxide (PO) to obtain poly(propylene oxide) grafted GO (GO-g-PPO) composites. The GO-g-PPO-16 composites are served as cross-linkers to prepare PU/GO-g-PPO-16 composite anticorrosive coating. Anticorrosive properties of the composite coating are greatly improved by filling a very little amount of GO-g-PPO-16 composites in PU matrix. The resistance of PU/0.08 GO-g-PPO-16 composite coating is 50 times of magnitude higher than that of neat PU coating. Abstract: Herein, polyurethane (PU)/poly(propylene oxide) grafted graphene oxide (GO-g-PPO) composite coating with anticorrosive properties was prepared by in situ polymerization. Results revealed that the anticorrosive properties of PU/GO-g-PPO-16 composite coating were greatly improved by the homogenous dispersion of GO-g-PPO-16 composites in PU coating. When the solid content of GO-g-PPO-16 composites was 0.08 wt. % in PU coating, the coating resistance was 50 times higher than that of PU coating after immersion in 3.5 wt. % NaCl (aq.) for 168 h.